The Effectiveness of Online Speaking Tasks (OST) on English Communication Ability of Thai EFL Undergraduates - Shimray, Yaruingam Phungshok (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
The purpose of this study was to investigate the effectiveness of online speaking tasks (OST) on the English communication ability of Thai EFL undergraduates. The study further examined students’ perspectives toward online oral presentation tasks. A questionnaire translated into the participants’ native language was utilized and distributed to collect data during the pandemic. The data were analyzed and interpreted using descriptive statistics, t-tests, and exploratory factor analysis (EFA). Four hundred and eighty-two students from Prince of Songkla University and Walailak University participated in this study. The study reveals that the use of technology is key to improving students’ English communication skills. Discourse analysis further showed that oral presentation tasks helped students improve their English communication skills. Pronunciation activity was the most difficult task students faced. It is strongly recommended that online learning through technology could be incorporated to complement the in-person learning environment.